Efektifitas Edukasi Kesehatan Seksual dan Reproduksi Pranikah terhadap Pengetahuan Siswa/i SMAN 1 Kakap Kubu Raya - Lidia Hastuti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Various efforts have been made by the government to reduce the number of young marriages, but this problem still exists. Provision of information needs to be done to increase students' knowledge about sexual/reproductive health, prevention of premarital sexual behavior and sexually transmitted infections. Provision of information can be done by providing direct information and other promotional media such as distributing leaflets. Universities can contribute to efforts to prevent the risk of young marriage by making health promotion efforts through education to students. Care for society program to increase knowledge about reproductive health, premarital sexual health, prevent risky sexual behavior and sexually transmitted infections in adolescents. Promotion efforts can be packaged by providing education with the theme of this activity being